Padrões morfológicos na venação alar de espécies de Tetragona Lepeletier & Serville, 1828 do grupo clavipes (Hymenoptera: Apidae: Meliponini) - Santos, Isamara S. dos; Nogueira, David S.; de Castro, Ivan; Teixeira, Juliana S. G.; Freitas, Geusa S. de; de Oliveira, Marcio L. (Entomological Communications, 2021)
Tetragona Lepeletier & Serville, 1828 (Hymenoptera: Apidae) is a genus of stingless bees widely distributed in Brazil. It has 15 species distributed in the Neotropics, from Mexico to Uruguay, nine of which are found in Brazil. However, Tetragona elongata (Lepeletier & Serville, 1828), a species known only from the Southeast region and which had been synonymized with Tetragona clavipes (Fabricius, 1804), was revalidated without any justification. The aim of this study was to test whether the morphometrics analysis of the wings is efficient in the diagnosis of the species of this genus, in addition to testing the validity of the revalidation mentioned above. This technique was applied by accessing the right forewings of 660 workers of T. clavipes, T. elongata e T. quadrangula (Lepeletier, 1836), from five Brazilian collections. For the geometric morphometric analysis, 12 landmarks were selected. The software MorphoJ version 1.6 was used to do Discriminant Function analysis (1000 replications) and Canonical Variation Analysis (CVA). Between T. clavipes and T. elongata, there was a 100% variance between species (canonical variation analysis), suggesting that it may be an indication of speciation. Even though T. elongata has been revalidated, it still has overlapped with T. clavipes, which indicates to be the same species. Taxonomic studies are needed to synonymize them.